Hexacyanoferrates and bentonite as binders of radiocaesium for reindeer - Hove, Knut; Staaland, Hans; Pedersen, Øyvind (Rangifer, 1991)
The effects of varying doses of caesium binders (Bentonite and several forms of iron-hexacyanoferrates) on radiocaesium accumulation in red blood cells and on radiocaesium transfer to urine and faeces were studied in feeding experiments with reindeer calves. The caesium binders were added to a ration of lichen (containing 9.5 kBq of 134Cs+137Cs originating from the Chernobyl accident) and fed together with a pelleted reindeer feed (RF-71) for 42 days. A 50% reduction in red blood cell radiocaesium concentration was obtained with a daily dose of 1 mg/kg body weigth of ammoniumironhexacyanoferrate (AFCF) and with 500 mg/kg of bentonite. Three mg/kg of AFCF or 2 g/kg of bentonite reduced both urinary excretion and RBC concentrations with more than 80%. It is concluded that iron-hexacyanoferrates, as a result of their high caesium binding capacity, are particularly useful as caesium binders for free ranging ruminants like the reindeer. Hexacynoferrater og bentonitt som bindere av radiocesium i rein Abstract in Norwegian / Sammendrag: Effekten av bentonitt og ulike typer jernhexacyanoferrater (Berlinerblått) på akkumulering av radioaktivt cesium i røde blodlegemer og på utskilling av radioaktivt cesium i urin ble undersøkt i foringsforsøk med reinkalver. Cesiumbinderne ble gitt daglig sammen med lav som inneholdt 9.5 kBq 134Cs+137Cs fra Tsjernobyl ulykken, og 1 kg reinfor (RF-71) i en periode på 42 dager. En daglig dose på 1 mg/kg kroppsvekt av ammoniumjernhexacyano-ferrat (AFCF) reduserte radiocesiuminnholdet i blodlegemer med 50%, mens en dose pa 500 mg/kg bentonitt var nødvendig for å oppnå samme effekt. Tre mg/kg AFCF eller 2 g/kg/bentonitt var nødvendig for å oppnå mer enn 80% reduksjon i radiocesium konsentrasjonen i blodlegemer og i radiocesium utskilling med urinen. På grunn av de små daglige mengder som kreves er jern-hexacyanoferratene spesielt velegnete som cesiumbindere for beitedyr.